Evaluation of different Mediterranean essential oils as prophylactic agents in anisakidosis - Magdalena Gómez-Mateos Pérez; Concepción Navarro Moll; Gema Merino Espinosa; Adela Valero López (Taylor & Francis Group, 2017)
Context: Anisakis Dujardin 1845 (Anisakidae) nematodes can cause gastrointestinal and allergic diseases when humans eat raw or undercooked seafood containing larvae. There is currently no drug available in the market against this parasitic disease, and the study of plant-derived molecules could be useful in the discovery of effective compounds. Objective: This research assesses the biocidal activity of a range of essential oils (EOs) from some Mediterranean plants against larvae found in the musculature of fresh fish. Materials and methods: EOs composition was analyzed by gas chromatography-mass spectroscopy. All the EOs were diluted at 5% v/v in olive oil to cover the fish with the solutions for 24 h. The larvae that abandoned the muscle and the larvae obtained from the artificial digestion of the fish were collected. Controls were carried out in parallel. Furthermore, Wistar rats were infected with the live larvae collected from the in vitro trials in order to find any larvae that may have penetrated the gastrointestinal wall. Results: Between 60.8% and 87.6% of parasites treated with EOs abandoned the fish muscle, and the highest in vitro mortality rate was achieved with oregano EO (53.9%). Rats previously treated with oregano, cumin and Spanish lavender EOs showed no detectable lesions in the digestive tract due to the infection with larvae. Conclusions: Oregano (Origanum vulgare L. Lamiaceae), cumin (Cuminum cyminum L. Apiaceae) and Spanish lavender (Lavender stoechas L. Lamiaceae) EOs could be used as promising ingredients in the development of products for the control of anisakiasis.